The nonlocal boundary problem with perturbations of antiperiodicity conditions for the elliptic equation with constant coefficients - Baranetskij, Ya.O.; Ivasiuk, I.Ya.; Kalenyuk, P.I.; Solomko, A.V. (Carpathian Mathematical Publications, 2018)
In this article, we investigate a problem with nonlocal boundary conditions which are perturbations of antiperiodical conditions in bounded $m$-dimensional parallelepiped using Fourier method. We describe properties of a transformation operator $R:L_2(G) → L_2(G),$ which gives us a connection between selfadjoint operator $L_0$ of the problem with antiperiodical conditions and operator $L$ of perturbation of the nonlocal problem $RL_0=LR.$ Also we construct a commutative group of transformation operators $Γ(L_0).$ We show that some abstract nonlocal problem corresponds to any transformation operator $R \in Γ(L_0):L_2(G) → L_2(G)$ and vice versa. We construct a system $V(L)$ of root functions of operator $L,$ which consists of infinite number of adjoint functions. Also we define conditions under which the system $V(L)$ is total and minimal in the space $L_{2}(G),$ and conditions under which it is a Riesz basis in the space $L_{2}(G)$. In case if $V(L)$ is a Riesz basis in the space $L_{2}(G),$ we obtain sufficient conditions under which the nonlocal problem has a unique solution in the form of Fourier series by system $V(L).$